Evidence-based commissioning in the English NHS: who uses which sources of evidence? A survey 2010/2011. Issue 5 (16th May 2013) - Clarke, Aileen; Taylor-Phillips, Sian; Swan, Jacky; Gkeredakis, Emmanouil; Mills, Penny; Powell, John; Nicolini, Davide; Roginski, Claudia; Scarbrough, Harry; Grove, Amy
Abstract : Objectives: To investigate types of evidence used by healthcare commissioners when making decisions and whether decisions were influenced by commissioners' experience, personal characteristics or role at work. Design: Cross-sectional survey of 345 National Health Service (NHS) staff members. Setting: The study was conducted across 11 English Primary Care Trusts between 2010 and 2011. Participants: A total of 440 staff involved in commissioning decisions and employed at NHS band 7 or above were invited to participate in the study. Of those, 345 (78%) completed all or a part of the survey. Main outcome measures: Participants were asked to rate how important different sources of evidence (empirical or practical) were in a recent decision that had been made. Backwards stepwise logistic regression analyses were undertaken to assess the contributions of age, gender and professional background, as well as the years of experience in NHS commissioning, pay grade and work role. Results: The extent to which empirical evidence was used for commissioning decisions in the NHS varied according to the professional background. Only 50% of respondents stated that clinical guidelines and cost-effectiveness evidence were important for healthcare decisions. Respondents were more likely to report use of empirical evidence if they worked in Public Health in comparison to other departments (p<0.0005, commissioning and contracts OR 0.32, 95%CI 0.18 to 0.57, finance OR 0.19, 95%CI 0.05 to 0.78, other departments OR 0.35, 95%CI 0.17 to 0.71) or if they were female (OR 1.8 95% CI 1.01 to 3.1) rather than male. Respondents were more likely to report use of practical evidence if they were more senior within the organisation (pay grade 8b or higher OR 2.7, 95%CI 1.4 to 5.3, p=0.004 in comparison to lower pay grades). Conclusions: Those trained in Public Health appeared more likely to use external empirical evidence while those at higher pay scales were more likely to use practical evidence when making commissioning decisions. Clearly, National Institute for Clinical Excellence (NICE) guidance and government publications (eg, National Service Frameworks) are important for decision-making, but practical sources of evidence such as local intelligence, benchmarking data and expert advice are also influential. New Clinical Commissioning Groups will need a variety of different evidence sources and expert involvement to ensure that effective decisions are made for their populations.